2013
DOI: 10.3928/01477447-20130222-09
|View full text |Cite
|
Sign up to set email alerts
|

Flexion-distraction Injuries in Children and Adolescents

Abstract: Flexion-distraction injuries represent an uncommon pattern of injury in the pediatric population. Although this is a well-studied topic in adults, the literature on such injuries in children and adolescents is relatively sparse, with only low levels of evidence available to guide treatment. These injuries carry a high rate of concomitant injuries and a high morbidity and mortality in this population. Proper understanding of these complex injuries is important to ensure proper management and avoid complications. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Postoperative care involved thoracolumbar-sacral orthosis (TLSO) for early ambulation, starting immediately after surgery and continuing for three months. The patient's positive recovery highlights the value of a team-based approach to complex spinal injuries in adolescents [ 3 , 19 ]. The necessity to document and disseminate surgical strategies and outcomes is also emphasized, given the relative scarcity of adolescent-focused spinal injury literature [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative care involved thoracolumbar-sacral orthosis (TLSO) for early ambulation, starting immediately after surgery and continuing for three months. The patient's positive recovery highlights the value of a team-based approach to complex spinal injuries in adolescents [ 3 , 19 ]. The necessity to document and disseminate surgical strategies and outcomes is also emphasized, given the relative scarcity of adolescent-focused spinal injury literature [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These injuries often disrupt the Posterior Ligament Complex (PLC), a critical component in maintaining spinal stability [ 1 , 2 ]. The adolescent population presents a unique set of challenges due to their growing anatomy, making the management of such injuries considerably complex [ [3] , [4] , [5] , [6] ]. Surgical restoration of spinal stability and prevention of further neurological deterioration is imperative to promote an optimal recovery trajectory and improve the quality of life of affected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…20 Small-sized studies initially suggested that thoracolumbar compression fracture injuries predominated, but most of these studies did not employ MRI examination, whereas a more recent retrospective study which included MRI, reported a 1.5% incidence of spinal injury in 726 cases of NAI between 2003 and 2011 which were predominantly ligamentous injury. 21 During the study period, NAI was the cause of the spinal injury in 11/342 (3.2%) patients suggesting that the true prevalence of spinal injury in NAI is higher if MRI is routinely employed. Importantly, all the NAI-spinal injury patients were <2 years old accounting for 38% of the cases of spinal injury in this age group, as common as from RTAs.…”
Section: Mechanism Of Injurymentioning
confidence: 93%
“…Burst type fractures are usually seen in the older child/adolescent ( Figure 10) whilst the rarer flexion-distraction injuries do not have a predilection for different age groups. 36 Spinal manifestations of child abuse sequelae may be seen in the growing spine, characteristically in the thoracolumbar spine as a result of hyperflexion-extension injury at multiple consecutive levels. Hobbs demonstrated this in a 6-year-old with contiguous anterosuperior vertebral corner defects with narrowed intervertebral disc heights in the lower thoracic and upper lumbar region as characteristic evidence of child abuse.…”
Section: Fracturesmentioning
confidence: 99%